AN ANALYSIS OF THE STRATEGIES USED IN TRANSLATING IDIOMS IN INDONESIA INTO ENGLISH FOUND IN INDONESIAN LEGENDS - Donny Bhaskara Wicaksono; erly Wahyuni (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
In this global era, due to the growth of science, information, technology, and other people needs, translation becomes necessary in rendering information between languages. However, the process of translating is not as simple as switching the meaning of word for word based on the literal context.Idioms are one of the most problematical components of language. Idioms cannot be easily translated because of their unpredictable meaning and grammar. The purpose of this study is to find out; (1) the idiomatic expressions which are found in Indonesian Legends, (2) the meaning of the idiomatic expressions found in Indonesian Legends, and (3) the various strategies which are used in translating idioms in Indonesia into English found in Indonesian Legends.The descriptive qualitative research design, in the form of document analysis, was employed in this study. The instruments to collect the data were documents and expert opinion. Moreover, the documents consisted of the Bahasa Indonesia (Source Text) and English (Target Text) translation versions of five Indonesian Legends, namely; Batu Kuwung, Batu Menangis, Gunung Merapi, Tangkuban Perahu and Candi Prambanan. This study revealed that idiomatic expression translation strategy by paraphrasingwas the most dominant strategy used by the translator in translating the idiomatic expressions found in five Indonesian Legends (eleven out of eighteen cases). Meanwhile, the second most common strategy was translating by omission (six out of eighteen cases).  The last was the strategy of using an idiom of similar meaning and form which only one out of eighteen cases. Thus, it can be concluded that the translator only applied three strategies out of the main five strategies of translating idiomatic expression suggested by Baker.